Supercritical water oxidation of hazardous waste: process enhancement and reactor design - Al-Atta, Ammar Jaber (2018)
The work presented in this thesis is focused on two specific areas of supercritical water oxidation (SCWO). Firstly, the design and testing of an innovative anticorrosive reactor design that can be used for the SCWO of hazardous organic waste. Secondly, exploiting the merits of counter current mixing reactor in combining two processes; Supercritical water oxidation (SCWO) and supercritical water hydrothermal synthesis (SCWHS) in one reactor. In Chapter 1, an introduction to supercritical fluid and supercritical water oxidation is given, followed by a brief account of the main problems associated with SCWO. This includes a review of the experience to date, with different reactor designs for corrosion control. This Chapter also provide an introduction to hydrothermal methodology and continuous flow reactor design for nanoparticle production, along with the aims and objective of this PhD. Chapter 2 details the components and construction of the experimental rigs used in this thesis. Additionally, this Chapter presents the principles behind the main analytical techniques used throughout this work, along with the definition of some important parameters. Chapter 3 reports the use of a physical modelling approach to assess mixingdynamics inside three different types of reactor where supercritical water is mixed with a second colder, waste containing, effluent flow. Physical or `pseudo'modelling was used to simulate the general flow patterns and mixing regimes in transparent pseudo reactors (to allow visualization). Towns water was used to simulate the supercritical water flow and 40% w/w aqueous sucrose solution to simulate the cold aqueous effluent flow. This visual technique allowed the quantification of mixing efficiency, as well as identification of issues such as flow recycling, stagnant zones, and other inconsistencies in the mixing dynamics. An upwards co-current protected wall reactor arrangement provided the `best' mixing i.e. with minimal wall contact during the downstream oxidation process. A combined process of SCWO and SCWHS in a continuous counter current reactor is the focus of Chapter 4. Acrylic acid was chosen as a model compound to represent an organic wastewater and the effects of the reaction temperature, residence time, oxidant ratio and acrylic acid concentration on chemical oxygen demand (COD) were all investigated. Two different experimental configurations for oxidant delivery were carried out in `pre-heated' and `non-preheated' oxidant configurations. With a stoichiometric excess of 100% oxygen, COD reduction levels of 80% (non-preheated) and 15% (preheated) were achieved with very short residence times. SCWHS was achieved through the addition of small amounts of various soluble metal salts in the cold up flow resulted in nanoparticles forming which increased the reaction rate and hydrothermal oxidation efficiency. The addition of small amounts of chromium nitrate (>5mM) results in nearly 100% COD reduction at 380C and residence times of 0.75 seconds. The potential economic benefits of combining the two processes together, in the different configurations, were also evaluated. In Chapter 5, The results of the catalytic oxidation in supercritical water of a non-biodegradable and highly toxic organic compound (phenol) are presented. The reactions were studied in a continuous counter current reactor through the in-situ formation of Fe2O3 catalyst. The preliminary results showed that catalytic non-preheated oxidant configuration resulted in increased COD removal when compared to other oxidant delivery methods. It was shown that temperatures below 400C could be used to decompose these compounds into final product and that complete conversion of COD could likely be expected within less than 1 second. It was demonstrated that SCWO combined with SCWHS is a feasible and cost-effective alternative for the destruction of contaminants in water. In Chapter 6, A laboratory-scale protected wall reactor rig was designed, constructed, tested, and operated to validate the pseudo modelling for application to SCWO. SEM, SEM/EDS, and XRD results showed that 1 meter long protected wall reactor was divided into two regions. 25% of the reactor length was protected by the flow of clean supercritical water. Near complete removal of the organic content of 2,4-DCP was obtained at mild operating conditions. To conclude, a summary of the work detailed in this thesis is delivered in Chapter 7. The most pertinent findings from this work are put forward, followed by a discussion of future work which could lead on from this thesis.